Hydrogen production from the acetic acid steam reforming over bimetallic nickel-cobalt supported on lathanum (III) oxide catalyst - Nabgan, Walid (2013)
Hydrogen is recognized as a sustainable and renewable energy carrier for transportation. The development of environmental friendly and cost effective hydrogen producing become the main challenge in this area. This work, catalytic steam reforming of acetic acid over bimetallic Nickel-Cobalt (Ni-Co) supported on Lanthanum (III) Oxide (La2O3) was studied. The objectives of this study are to obtain a highest hydrogen production and to study the effects of reaction condition such as reaction temperature; pressure and effect the quantity of catalyst to the hydrogen production. Also, to study the effect of Silicon Carbide (SiC) dilution with catalyst at different temperature. The catalysts are prepared by impregnation method. The catalyst performance tests are carried out in a fixed bed reactor at atmospheric pressure and temperature from 500°C to 700°C at increment of 50°C, flow rate range between 0.1 to 0.49 mL/min, acetic acid concentration in range of 10 to 40 wt. % and the weight of catalyst between 0.1 to 0.3 g. It was found that the hydrogen production dropped by increasing of acetic acid concentration and the optimum condition is at temperature of 550 oC and 0.25 g catalyst whereas 600 oC while the SiC was used as a catalyst dilution and achieved 98.89% acetic acid conversion. A series of acetic acid flow rate and a series of amount of catalyst supported on La2O3 with and without SiC dilution have been investigated at 600 oC, 1 atm and 10 wt.% of acetic acid. Catalyst at 0.25 gr and 0.36 mL/min of acetic acid flow rate exhibits the best performance; it is given of 0.61 mole fraction of hydrogen